THE CURRENT LEARNING METHODOLOGY AND IT’S FUTURE TRENDS - Guo Liyuan (International Journal of Innovative Technologies in Social Science, 2024)
The future of any country’s development the main determining factor is education. The main goal of education is for student’s successful training, intellectual, moral, with appropriate physical capabilities and humaneness respect, study, work, and live independently is to develop into a capable individual. Nowadays, the development of technology changes people’s lives technology while making it easier and easier of a person who wants to receive services based on progress arouses interest. It is also in education and depends. [1] Technological innovation fundamentally transforms education, reshaping the needs and skills required for present and future workplaces. Building a future-ready education system requires consistent delivery of 21st-century curriculum and inclusive models that provide a strong foundation for lifelong adaptation and new skills development, with specialized education focusing on skills that are in demand in the real world. This disconnect between employer needs and talent pools must be addressed. This study on where and how modern learning methods and trends are headed in today’s Industry 4.0 transition is based on the predictions of a wide range of experts from the World Economic Forum’s expert network and the Organization for Economic Co-operation and Development (OECD)’s Education and It was developed based on the initiative of the Future of Skills 2030 project.